Learning by Contributing: Gaining Competitive Advantage Through Contribution to Crowdsourced Public Goods - Nagle, Frank (Organization Science, 2018)
As the economy becomes more information based, firms are increasingly using crowdsourced public goods as inputs for innovation and production. Counterintuitively, some firms pay their employees to contribute to the creation of these goods, which can be used freely by their competitors. This study argues that such firms learn by contributing as they receive feedback from the crowd of more experienced users and are therefore able to better capture value from using the goods. Data on firm contributions to open source software (OSS), an important crowdsourced public good, is used to test the theoretical predictions. Using matching and panel data methods to help address endogeneity concerns, this study shows that contributing firms capture up to 100% more productive value from usage of OSS than their free-riding peers. Furthermore, this paper examines what types of contributions are most beneficial and in what technological environments such learning can best be applied.